FTO (Freedom to Operate) in the Pharmaceutical Industry - Nonaka, Hirotaka (Munich Intellectual Property Law Center - MIPLC, 2018)
FTO licensing in the pharmaceutical industry deserves special consideration because of the large economic scale of the market, expensive cost of R&D, extremely low success rate, and easy duplication of the drug. Taking these unique aspects into consideration, the author first explaines how to perform a good FTO search and conclude an appropriate FTO licensing agreement, and then points out two issues; (i) the issue of FTO licensing and EU competition, especially the unreasonable application of the Guideline, and (ii) the issue of FTO licensing and differentiating between a bio venture company and a pharmaceutical company. Solutions for these issues are proposed.